Mother-Offspring Relations: Prey Quality and Maternal Size Affect Egg Size of an Acariphagous Lady Beetle in Culture - Eric W. Riddick; Zhixin Wu (Psyche: A Journal of Entomology)
We investigated mother-offspring relations in a lady beetle Stethorus punctillum Weise that utilizes spider mites as prey. Our objectives were to determine if (1) prey quality affects egg size, (2) maternal size correlates with egg size, and (3) egg size affects hatching success. We fed predators spider mites Tetranychus urticae Koch from lima bean Phaseolus lunatus L. foliage in the laboratory. Mothers of unknown body size offered high rather than low quality spider mites since birth produced larger eggs. Mothers of known body size offered only high quality spider mites, produced eggs of variable size, but mean egg size correlated positively with hind femur length. Mothers laid their eggs singly, rather than in batches, and eggs were large relative to femur size. Egg size did not affect hatch success; mean hatch rate exceeded 95% regardless of egg size. In conclusion, the quality of prey consumed by S. punctillum mothers while in the larval stage can affect their size as adults and, consequently, the size of their eggs. The behavior of laying eggs singly, the positive relationship between maternal size and mean egg size, and the high rate of egg hatch suggest that S. punctillum mothers invest heavily in offspring.